Crime and Inequality - Hagan John; Peterson Ruth D (Stanford University Press, 1995)
This volume seeks to discover how and why inequality affects the patterning of crime and criminal justice, with special emphasis on important questions that have been ignored or have received inadequate attention. Introduction, Criminal Inequality in America, Toward a Theory of Race and Crime and Urban Inequality, Unemployment and Crime Rate Fluctuations in the Post-World War II United States: Statistical Time-Series Properties and Alternative Models, Ethnography and Inequality and Crime in the Low-Income Community, Age-Inequality and Property Crime: The Effects of Age-Linked Stratification and Status-Attainment Processes on Patterns of Criminality Across the Life Course, Crime and Inequality in Eighteenth-Century London, Gender and Race and the Pathways to Delinquency: An Interactionist Explanation, Gender Inequality and Violence Against Women: The Case of Murder, Crime and Inequality and Justice in Eastern Europe: Anomie and Domination and Revolutionary Change, The Engineering of Social Control: The Search for the Silver Bullet, Law and Crime and Inequality: The Regulatory State, Inequality and Republican Criminology, Notes, Bibliography, Index.